PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI 10 TAMBUN SELATAN - Niken Yuliyanti; Hasanuddin Hasanuddin; Jumawan Jumawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine whether Workload and Compensation have an influence on Job Satisfaction of Teachers at SMP N 10 Tambun Selatan. The research method used in this study is a quantitative method. The sampling technique in this study used a saturated sample or census of 43 respondents. The data collection technique was in the form of a questionnaire arranged in several statements and measured using the Likert Scale. Data analysis used in this test used the Structural Equitation Model (SEM). Data was processed using SMART PLS 4.0. The results of this study indicate that (1) Workload has a positive and significant effect on Job Satisfaction of Teachers at SMP N 10 Tambun Selatan, and (2) Compensation has a positive and significant effect on Job Satisfaction of Teachers at SMP N 10 Tambun Selatan.